IMPLEMENTASI PENERAPAN ISLAMIC CORPORATE SOCIAL RESPONSIBILITY PADA SPIRITUAL COMPANY WAROENG GROUP PERSPEKTIF MAQASID AL-SYARIAH - Putri, Nurul Wulandari (Valid Jurnal Ilmiah, 2019)
Islam highly concerns with the social and environmental benefit in which it has a complete guideline for its followers including the guideline on how a business is run. This research aims to describe the management of Islamic Cooperate Social Responsibility on the Spiritual Company Waroeng Group in the perspective of Al-Maqasah Al Syaria. This is a descriptive- qualitative research using the approach of fenomenalogi aimed to describe the realty on the management of Islamic Corporate Social Responsibility that later was analyzed or measured by means of a number of theories relevant with the issues concerned. In addition, this research used the analysis of Maqasid Al-Syariah to observe how urgency is prioritized by company in management. Based on the result of this research, it can be found that the management of Islamic Corporate Social Responsibilityconducted by Spiritual Company Waroeng Group is not optimally implemented yet from the regulation. It was also in how the principles of management of Islamic Corporate Social Responsibility were conducted properly.  On the other hand, for the implementation of the principles of Maqasid Al-Syariah in the management of Islamic Corporate Social Responsibility conducted by Spiritual Company Waroeng Group recently has been done by concerning with its urgency. Of those five basic principles of Maqasid Al-Syariah: Heredity Protection, brain, pride and soul, religion and wealth, it was only three principles that have been implemented optimally including protection towards brain, religion and wealth.